Professor Henry Wasser and the Henry Wasser Travel Grant for Ph.D. and MA Students in NAAS - Øverland, Orm (American Studies in Scandinavia, 2017)
Thanks to the generosity of Solidelle Fortier Wasser and her son Professor Frederick Wasser NAAS now has a travel grant named for their husband and father, Professor Henry Wasser, for the participation of PhD and MA students in our national and Nordic conferences. Although dearly remembered by Norwegian Americanists of my generation, Henry Wasser may need an introduction to my younger colleagues in NAAS. The following is a brief outline of his participation in and contribution to American Studies in Norway in the early 1960s as well as a note on the continued involvement of the Wasser family in American Studies in the Nordic countries.